Comparative Study of Electronic Waste Management in Developed Countries and Indonesia - Raharjo, Slamet; Utomo, Al Hadi (Andalasian International Journal of Applied Science, Engineering and Technology, 2021)
Electronic waste management in Indonesia is currently not a major concern for various parties and is relatively left behind when compared to developed countries. This study aims to evaluate the existing conditions of electronic waste management in Indonesia and compile recommendations for electronic waste management programs in Indonesia. This research was conducted by collecting primary data from questionnaires and collecting secondary data from the literature on electronic waste management in developed countries (United States, Japan, and Switzerland) and Indonesia. The collected data were compared and analyzed for compiling strategy in the SWOT (Strengths, Weaknesses, Opportunities, Threats). Recommendation programs for electronic waste management in Indonesia were established based on SWOT Matrix. The evaluation results show that the existing conditions of electronic waste management in Indonesia are lagging compared to developed countries. The management recommendation program provided is the 4R programs (Reduce, Reuse, Recycle and Remove) for electronic waste; Dropbox to collect electronic waste; Development of formal electronic waste management infrastructure; Industrial revitalization / private electronic waste recycling facilities; Development of electronic waste landfill; Application of economic instruments for electronic manufacturers; Extended Producer Responsibility (EPR) for electronic equipment; Trade-in for all electronic products; and cooperate with the informal sector. Keywords: Developed countries, Electronic waste, Program recommendations, SWOT analysis, Waste management.